Intrinsic Study and Moral Values in The Folklore of Karo Deleng Pertektekken - Sari, Ferbina (Institute of Computer Science (IOCS), 2020)
Folklore is oral literature that is believed by the local community where the folklore developed, although the truth of the story is not certain, of course behind the folklore there are lessons and examples to be better. The selection of the Deleng Pertektekkenini rayat story comes from Doulu Village, Berastagi District, Karo Regency and is an oral literature of the Karo people. In this study, the theoretical basis used is the study of intrinsic and moral values ??with qualitative methods. From the intrinsic research, the theme of the story is wealth and strength that blinds a father to his child, until finally the father regrets. The characters of the story are Guru Bidder Remai, Nini Kertah Ernala, the two daughters of Guru Petawar Remai, men from Tanah Karo, neighbors and the community Doulu Village. The setting / setting is Doulu Village and outside Doulu Village. The plot used is a forward plot that is in accordance with the time sequence of events from the beginning to the end of the story. The mandate in the Deleng Pertektekken folklore teaches us not to be arrogant about what we have and of course, mutual respect between fellow human beings. Then the moral values ??are found as follows: first, individual moral values ??include being willing to sacrifice, being honest, fair and wise, respecting and appreciating, working hard, and being humble. The two social moral values ??include cooperation, being helpful, loving, sociable, and caring for the fate of others. Third, religious moral values ??include believing in God, believing in God's power, surrendering to God / trusting in God.